2014
DOI: 10.1002/j.1532-2149.2014.487.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of training on corticomotor excitability in clinical neck pain

Abstract: Neck training reduced neuroplastic responsiveness of corticomotor pathways in neck pain patients in contrast to knee pain patients and pain-free participants. Increased attention to adaptive and maladaptive neuroplastic responses induced by training may prove valuable in the process of optimizing clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…In the present study (Rittig‐Rasmussen et al., ), the authors found that patients with neck pain who underwent a 20‐min weight lifting training session actually presented a decrease in MEP amplitudes compared with baseline values, which could be detected 30 min after training. However, knee pain patients who also underwent the same training programme presented an increase in MEP amplitudes up to an hour after training.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…In the present study (Rittig‐Rasmussen et al., ), the authors found that patients with neck pain who underwent a 20‐min weight lifting training session actually presented a decrease in MEP amplitudes compared with baseline values, which could be detected 30 min after training. However, knee pain patients who also underwent the same training programme presented an increase in MEP amplitudes up to an hour after training.…”
supporting
confidence: 52%
“…In this issue, you will find a paper by Rittig‐Rasmussen et al. titled ‘Effect of training on corticomotor excitability in clinical neck pain’ (Rittig‐Rasmussen et al., ). In this study, the authors compared the effects of motor neck training on corticomotor excitability in patients with neck pain, patients with knee pain and healthy volunteers.…”
mentioning
confidence: 99%
“…Our data indicated that pain induction resulted in a significant decrease in MEP amplitude in the absence of pcTBS intervention. This finding is consistent with previous studies in which MEP amplitude was reduced by chronic pain (Lefaucheur et al, 2006;Cosentino et al, 2014;Rittig-Rasmussen et al, 2014;Parker et al, 2016). Reduced motor cortical output is associated with the imbalance of neurotransmission in the central nervous system evoked by the ascending transmission of nociception.…”
Section: Discussionsupporting
confidence: 93%
“…The majority of the included articles focused on chronic pain conditions (n = 10) (Baarbe et al, 2018 ; Hoeger Bement et al, 2014 ; Masse-Alarie et al, 2016 , 2017b ; Mendonca et al, 2016 ; Parker et al, 2017 ; Rittig-Rasmussen et al, 2014a ; Schwenkreis et al, 2011 ; Tsao et al, 2010 ; Vallence et al, 2013 ), and the remaining articles focused on acute pain in healthy individuals (n = 7) (Boudreau et al, 2007 ; Dancey et al, 2019 ; De Martino, Petrini, et al, 2018 ; De Martino, Zandalasini, et al, 2018 ; Ingham et al, 2011 ; Mavromatis et al, 2017 ; Rittig-Rasmussen et al, 2014b ). The chronic pain conditions included headache (n = 1), pain in the neck region (n = 2), lower back pain (n = 3), painful hand arthritis (n = 1) and fibromyalgia (n = 3).…”
Section: Resultsmentioning
confidence: 99%